The application of a surface response methodology in the solar/UV-induced degradation of dairy wastewater using immobilized ZnO as a semiconductor - Lamas Samanamud, Gisella R.; Izario Filho, Helcio J.; Loures, Carla C. A. [UNESP]; Oliveira, Ivy S.; Souza, Andre L.; De Freitas, Ana Paula B. R. [UNESP]; Pei, Ruoting (Hindawi, 2013)
An Advanced Oxidation Process (AOPs) was carried out in this study with the use of immobilized ZnO and solar/UV as an energy source to degrade dairy wastewater. The semibatch reactor system consisted of metal plate of 800 × 250 mm and a glass tank. The reaction time was of 3 h for 3 L of dairy wastewater. Experiments were performed based on a surface response methodology in order to optimize the photocatalytic process. Degradation was measured in percentage terms by total organic carbon (TOC). The entry variables were ZnO coating thickness and pH, using three levels of each variable. The optimized results showed a TOC degradation of 31.7%. Optimal parameters were metal-plate coating of 100 m of ZnO and pH of 8.0. Since solar/UV is a constant and free energy source in most tropical countries, this process tends to suggest an interesting contribution in dairy wastewater treatment, especially as a pretreatment and the optimal conditions to guarantee a better efficiency of the process. © 2013 Gisella R. Lamas Samanamud et al.